2003
DOI: 10.1029/2002jd003028
|View full text |Cite
|
Sign up to set email alerts
|

Transpiration peak over a hill evergreen forest in northern Thailand in the late dry season: Assessing the seasonal changes in evapotranspiration using a multilayer model

Abstract: [1] The seasonal changes in evapotranspiration over a hill evergreen forest in northern Thailand (18°48 0 N, 98°54 0 E), in the Asian monsoon region, were simulated using a multilayer model and the boundary conditions above the canopy. The simulation considered the uncertainty in the leaf area index (LAI) and physiological parameters for both photosynthesis and stomatal conductance models. The parameters were based on the estimated LAI and determined by referring to the measured net photosynthesis rate and sto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
102
0

Year Published

2006
2006
2017
2017

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 94 publications
(107 citation statements)
references
References 45 publications
5
102
0
Order By: Relevance
“…The evapotranspiration estimated by a multi-layer model forced by the observed radiation, leaf area index (LAI) and other realistic parameters revealed that a seasonally maximum evapo-transpiration appeared in the late dry season just before the monsoon onset (Fig. 7) when the ground surface was driest in the year (Tanaka et al 2003). A LSM study including the effect of root depth to pump up water in deep soil layer could well simulate this seasonal feature when the mean root depth was set at 6 m (Tanaka et al 2004;Tanaka and Hashimoto 2006).…”
Section: Role Of Vegetationmentioning
confidence: 99%
See 1 more Smart Citation
“…The evapotranspiration estimated by a multi-layer model forced by the observed radiation, leaf area index (LAI) and other realistic parameters revealed that a seasonally maximum evapo-transpiration appeared in the late dry season just before the monsoon onset (Fig. 7) when the ground surface was driest in the year (Tanaka et al 2003). A LSM study including the effect of root depth to pump up water in deep soil layer could well simulate this seasonal feature when the mean root depth was set at 6 m (Tanaka et al 2004;Tanaka and Hashimoto 2006).…”
Section: Role Of Vegetationmentioning
confidence: 99%
“…Vertical bars indicate ranges of 32 simulated values with the maximum and the minimum, respectively. (Tanaka et al 2003) tion of the atmospheric boundary layer (ABL), and relevant cloud processes at or above the ABL. Betts et al (1998) reviewed the overall possible interactive processes between land surface conditions and the ABL, and emphasized the importance of vegetation and related land cover/use differences on the ABL structure and cloud/precipitation process.…”
Section: Role Of Vegetationmentioning
confidence: 99%
“…Regarding the seasonal variations in ET, Tanaka et al (2008) reported that tropical evergreen forest in the mountainous area of the Chao Phraya river basin has a deep soil layer (∼ 5.3 m), which allows fairly steady evaporation throughout a year regardless of the amount of rainfall in different seasons and years (e.g. Tanaka et al, 2003), whereas for diverse land use in northern Thailand, Kim et al (2014) reported that ET becomes higher in the monsoon season than in the dry season with about 10 % interannual variations. Essentially the model behaves in a similar way; i.e.…”
Section: Water Balance Analysis Based On Long-term Rri Simulationmentioning
confidence: 99%
“…A contrast in soil moisture is clear before and after the monsoon in Thailand (Tanaka et al 2003). Figure 6b shows the simulated results in the same calm situation shown in Fig.…”
Section: Discussionmentioning
confidence: 69%
“…Air column should be almost saturated owing to a continuous supply of water vapor in large quantities. Therefore, clear diurnal variation in PWV tends to appear in the period before the monsoon, when the soil moisture is lowest around Thailand (Tanaka et al 2003).…”
Section: Discussionmentioning
confidence: 99%